STUDY OF THE ANTEROLATERAL LIGAMENT OF THE KNEE IN FORMALIN-EMBEDDED CADAVERS - Fardin,Paloma Batista Almeida (2017)
ABSTRACT Objective: To verify the incidence and characterize morphologically the anterolateral ligament of the knee (ALL) in cadaveric samples of the collection of the Laboratory of Anatomy of the Department of Morphology of the Universidade Federal do Espírito Santo. Methods: Dissections and cross sections were performed for mesoscopic analysis of the anterolateral region of 15 knees preserved in 4% formalin solution in order to identify the ALL. Results: After dissection of the skin and subcutaneous tissue of the knee anterolateral region, it was possible to identify the iliotibial tract (ITT), the patellar ligament and the femoral biceps tendon. The ITT was removed from the Gerdy tubercle and the following structures were visualized: knee joint capsule, fibular collateral ligament and popliteal tendon. However, the ALL was not identified in any of the samples. Conclusions: The ALL could not be identified in any of the specimens studied, either through dissection or mesoscopic analysis. Level of Evidence III, Diagnosis Studies - Investigation of an Exam for Diagnosis.